Penggunaan Media Permainan Ular Tangga Numerasi Sebagai Peningkatan Pemahaman Konsep Bilangan Anak Usia 6 Tahun di SDN 065 Kota Jambi - Hasni, Uswatul; Alim, Khairul; ., E.Febriyanti; Ramadani, Diva Tamara; Nasution, Puspa Emilia (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
This research was motivated by observational data that showed very low student numeracy results. To respond to this, researchers conducted classroom action research aimed at improving student learning outcomes. The location of this research was conducted at SDN 065 Jambi City. The purpose of this study is to describe: 1) develop a design of a 6-year-old number concept numeracy program, 2) implementation of a number concept numeracy program, 3) efforts to overcome Obstacles to the implementation of the numeracy program with numeracy snakes and ladders media. This study was conducted on grade 1 students with a total of 14 people. This study aims to measure numeracy ability in these students. The results of this study showed an increase in students' numeracy ability in the use of numeracy snakes and ladders learning media. With active media-based learning and educational games, students get a direct learning experience, so that learning is more interesting and can improve student learning outcomes. From the data obtained, it is recommended to teachers to use active learning media and educational games in numeracy development to improve student learning outcomes.